Oxidation of amino acids, peptides, and proteins : kinetics and mechanism - Sharma, Virender K. (Hoboken, N.J. : John Wiley & Sons, 2012)
This book summarizes the chemical mechanisms and detailed kinetics of amino acid and peptide oxidation to help understand how proteins break down or dissociate when under stress in biological and environmental systems so that new drugs and antioxidants may be developed. It provides a summary of fundamental information on the kinetics and mechanism of amino acids by various oxidants. It also discusses oxidative chemistry of amino acids, peptides, and proteins. This useful guide also provides problems and their solutions associated with amino acids, peptides, and proteins in the aquatic environment.
Reactive species -- Acid-base properties -- Halogenated species -- Reactive oxygen species -- Reactive inorganic oxy-species of C, N, S, and P -- High-valent Cr, Mn, and Fe species.
"Published online: 10 DEC 2012 06:17PM EST"--Home page (Wiley, viewed August 5, 2015).
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Amino acids -- Oxidation; Peptides -- Oxidation; Proteins -- Oxidation; Oxidation-Reduction.; Amino Acids -- metabolism; Environmental Pollutants -- chemistry; Peptides -- metabolism; Proteins -- metabolism; SCIENCE -- Chemistry -- Organic; Science; Amino Acids -- metabolism; Environmental Pollutants -- chemistry; Oxidation-Reduction.; Peptides -- metabolism; Proteins -- metabolism; Electronic books; Electronic books